Tinjauan Hukum Terhadap Pelanggaran Hak Cipta Game Online Bajakan Di Indonesia - Dito, Muhamad Fidel Raihan; Widyastuti, Sri; Awaka, Muhammad Qahar (Tanjungpura Legal Review, 2024)
AbstractThe abstract should be clear, concise, and descriptive. This abstract should provide a brief introduction to the problem, objective of the article, followed by a statement regarding the methodology (optional) and a brief summary of results. Abstracts are written in font arial 10 pt, Italic, single spacing in one paragraph and preferably not more than 300 words. This study aims to evaluate the regulation of game copyright in Law Number 28 of 2014 and assess the extent to which this regulation provides effective protection for game creators. The research method employed is Normative Legal Research using a Case Approach and Legal Approach. Analysis is conducted on legal regulations, government regulations, and technical regulations related to game piracy in Indonesia. Based on the research findings, several factors contribute to the occurrence of online game piracy, including the lack of clarity in regulations related to online games, ineffective law enforcement, and a lack of legal awareness among the general public. Additionally, there are shortcomings in regulations that are not specific enough regarding the circulation of online games, as well as a lack of effective mechanisms to address technological advancements in the gaming industry. Law enforcement concerning online game piracy also faces challenges, such as a lack of understanding and knowledge among law enforcement officials regarding online games. Efforts to enhance collaboration between law enforcement agencies, the government, and the gaming industry are necessary to address cases of copyright infringement in online games in Indonesia.AbstrakPenelitian ini bertujuan untuk mengevaluasi pengaturan hak cipta game dalam Undang-Undang Nomor 28 Tahun 2014 dan menilai sejauh mana pengaturan tersebut memberikan perlindungan yang efektif bagi pencipta game. Metode penelitian yang digunakan penulis adalah penelitian Hukum Normatif dengan menggunakan Pendekatan kasus dan Pendekatan undang-undang. Analisis dilakukan terhadap peraturan hukum, peraturan pemerintah, dan peraturan teknis yang berkaitan dengan game bajakan di Indonesia. Berdasarkan hasil penelitian menunjukkan bahwa terdapat beberapa faktor yang mendorong terjadinya pembajakan game online, seperti ketidakjelasan dalam pengaturan terkait game online, kurangnya penegakan hukum yang efektif, dan kurangnya kesadaran hukum dalam masyarakat. Selain itu, terdapat kekurangan dalam pengaturan yang belum cukup spesifik terkait peredaran game online dan belum adanya mekanisme yang efektif untuk menghadapi perkembangan teknologi dalam industri game. Penegakan hukum terkait pembajakan game online juga masih menghadapi tantangan, seperti kurangnya pemahaman dan pengetahuan penegak hukum tentang game online. Diperlukan upaya peningkatan kerjasama antara lembaga penegak hukum, pemerintah, dan industri game dalam menangani kasus-kasus pelanggaran hak cipta dalam game online di Indonesia.